2006
DOI: 10.1111/j.1556-4029.2006.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Imaging for Noninvasive Detection of Latent Fingerprints

Abstract: The capability of Fourier transform infrared (FTIR) spectroscopic imaging to provide detailed images of unprocessed latent fingerprints while also preserving important trace evidence is demonstrated. Unprocessed fingerprints were developed on various porous and nonporous substrates. Data-processing methods used to extract the latent fingerprint ridge pattern from the background material included basic infrared spectroscopic band intensities, addition and subtraction of band intensity measurements, principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 27 publications
3
81
0
1
Order By: Relevance
“…Advances in nanotechnological techniques enable the use of new methodologies for making and augmenting crime scene identifications [13][14][15]. Research into nanostructured particles [4, 16,17] has helped develop techniques with improved latent fingerprint development, though efficacy remains surface dependent [4,17].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in nanotechnological techniques enable the use of new methodologies for making and augmenting crime scene identifications [13][14][15]. Research into nanostructured particles [4, 16,17] has helped develop techniques with improved latent fingerprint development, though efficacy remains surface dependent [4,17].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The application of ATR-FT-IR imaging for the study of the chemical composition of various residues contained in adult fingerprints was demonstrated by Ricci et al 9 At crime scenes, marks developed on textured or patterned backgrounds may be difficult to visualize in situ, and therefore, it may be desirable to collect fingermarks from crime scenes so that they can be transported for further examination in a laboratory or in a fingerprint bureau. Traditionally, many fingermarks are developed at crime scenes by powdering (e.g., with aluminum flake powder) and are recovered for subsequent evaluation by lifting them from the surface on clear adhesive tape.…”
mentioning
confidence: 99%
“…Crane et al demonstrated the ability of IR HSI to detect latent untreated fingermarks on various porous backgrounds (copier paper, cigarette butt paper, U.S. dollar bill, postcard) and nonporous backgrounds (trash bags, a soda can, tape) [27]. Fingermarks on the soda can and a black trash bag were clearly visible when viewing the intensity band image at 9842 nm (asymmetric O-C-C stretch ester) (see Figure 7).…”
Section: Detection and Enhancement Of Untreated Fingermarksmentioning
confidence: 99%
“…Eccrine deposits mainly consist of amino acids, inorganic compounds, and proteins, while sebaceous material consists primarily of fatty acid esters [25]. The chemistry of these residues varies among individuals and it shows increasing amounts of sebaceous deposits with age [26,27]. Fingermark detection techniques aim to create contrast between the ridge details of a latent fingermark and the background on which it is located.…”
Section: Fingermarksmentioning
confidence: 99%
See 1 more Smart Citation